PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR BIOLOGI KELAS VII SMPN 3 LEMBANG JAYA KABUPATEN SOLOK TAHUN PELAJARAN 2013/2014 - Putri, Delfia; Nurhadi, Nurhadi; Fitriani, Vivi (STKIP PGRI Sumbar, 2014)
Â The basic of this study was influenced by the less of Biology achievement of students on average scores were under the standard criteria, specifically on Ecosystem subject at grade VII of second semester in SMPN 3 Lembang Jaya while the learning process still focus on teacher. There are many various models that can be used to make the centre learning be focus on student. For example, cooperative learning models by using Think Pair Share at grade VII of SMPN 3 Lembang Jaya, Solok on year 2013/2014. The purpose of this research was to know the effect of Think Pair Share strategy toward students Biology achievement at grade VII of SMPN 3 Lembang Jaya Solok. The type of this study was experimental research with registerd students of 2013/2014 at Â grade VII as the population. The designed of this study was Randomized Control Group Posttest only Design. According to the analysis results the average results on experimental class was 80,58 with reability 11,49, while the average results on controlling class was 70,73 with reability 11,55. From the t-test, it was resultedt-count= 3,05 and t-table= 1,67 it means that tcount>ttable, in case the hypothesis in level 95% can be accepted. It can be concluded that the application of cooperative learning by using Think Pair Share has positive effect toward students Biology achievement at grade VII in SMPN 3 Lembang Jaya, Solok on year 2013/2014.